Librarian's guide to online searching - Bell, Suzanne S. (Librarian's guide to., 2012)
"This complete guide provides librarians and students at every level of experience with proven strategies and tools for efficient online searching, covering commonly available subject databases and principles of effective searching"--Provided by publisher.